1998
DOI: 10.1530/eje.0.1390059
|View full text |Cite
|
Sign up to set email alerts
|

Unequal impact of age, percentage body fat, and serum testosterone concentrations on the somatotrophic, IGF-I, and IGF-binding protein responses to a three-day intravenous growth hormone-releasing hormone pulsatile infusion in men

Abstract: We here investigate the potential rescue of the relative hyposomatotropism of aging and obesity by 3-day pulsatile GHRH infusions (i.v. bolus 0.33 mg/kg every 90 min) in 19 healthy men of varying ages (18 to 66 years) and body compositions (12 to 37% total body fat). Baseline (control) and GHRHdriven pulsatile GH secretion (in randomly ordered sessions) were quantitated by deconvolution analysis of 24-h (10-min sampling) serum GH concentration profiles measured in an ultrasensitive (threshold 0.005 mg/l) chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 60 publications
3
43
0
Order By: Relevance
“…A similar inference was made for pulsatile GHRH-induced GH secretion in another analysis in aging men, which omitted L-arginine and included obese subjects (4). To the degree that L-arginine antagonizes hypothalamic somatostatin release, we infer that the negative relationship between combined L-arginine/ GHRH-stimulated GH secretion and AVF is not attributable solely to heightened somatostatin outflow.…”
Section: Discussionsupporting
confidence: 53%
“…A similar inference was made for pulsatile GHRH-induced GH secretion in another analysis in aging men, which omitted L-arginine and included obese subjects (4). To the degree that L-arginine antagonizes hypothalamic somatostatin release, we infer that the negative relationship between combined L-arginine/ GHRH-stimulated GH secretion and AVF is not attributable solely to heightened somatostatin outflow.…”
Section: Discussionsupporting
confidence: 53%
“…The magnitude of GH bursts correlates with somatic growth and hepatic actions of the hormone. Decreased pulsatility may contribute to decreased IGF-I concentration as observed in aged subjects (22,23). Pulses are generated by interactions among GHRH, ghrelin, and somatostatin under negative feedback control by IGF-I and GH (24).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The studies of larger numbers of obese and non-obese subjects indicated that IGF-I concentrations were negatively correlated with age and BMI; however, they were not associated with fat distribution, ie waist -hip ratio. 15 It is now generally accepted that the total IGF-I concentrations are normal or slightly reduced within the normal range in obesity despite the marked impairment of both basal and stimulated GH secretion. 29 No significant relation between fat distribution and IGF-I levels in the studies with large numbers of subjects may be due to inaccurate assessment of fat distribution such as waist -hip ratio.…”
Section: Discussionmentioning
confidence: 99%